2015
DOI: 10.1080/2162402x.2015.1029701
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 and CD8+PD1+ lymphocytes exist as targets in the pediatric tumor microenvironment for immunomodulatory therapy

Abstract: antibody; PD-1, programmed cell death 1; PD-L1, programmed cell death ligand 1; TIL, tumor-infiltrating lymphocyte.Recent monoclonal antibody trials targeting the PD1/PD-L1 immune-checkpoint pathway have shown remarkable success in treating adult malignancies, with PD-L1-expressing tumors showing the most objective response. However, little is known as to whether pediatric cancers have also adopted this immune evasion mechanism. We evaluated 115 pediatric tumors (taken at diagnosis) for PD-L1 expression and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
60
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 22 publications
0
60
5
Order By: Relevance
“…An early study did not identify PD-L1 expression in any of the 18 tested samples from neuroblastoma patients 40. In contrast, Chowdhury et al reported PD-L1 surface expression in 31 (72%) of 43 patient tumor samples,32 with lower survival in patients expressing PD-L1. Dondero et al confirmed that PD-1 expression is present in lymphocytes obtained from metastatic bone marrow samples, and that PD-L1 expression in tumor cells is inducible with interferon gamma 41.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…An early study did not identify PD-L1 expression in any of the 18 tested samples from neuroblastoma patients 40. In contrast, Chowdhury et al reported PD-L1 surface expression in 31 (72%) of 43 patient tumor samples,32 with lower survival in patients expressing PD-L1. Dondero et al confirmed that PD-1 expression is present in lymphocytes obtained from metastatic bone marrow samples, and that PD-L1 expression in tumor cells is inducible with interferon gamma 41.…”
Section: Introductionmentioning
confidence: 95%
“…In two of the larger studies to date of osteosarcoma, IHC analysis showed PD-L1 expression in 25%–47% of primary tumor samples, and tumors expressing PD-L1 were significantly more likely to have infiltrating immune cells, which often expressed PD-1 32,33. Importantly, PD-L1 expression correlated with worse event-free survival, and these findings are consistent with the concept that PD-L1 in tumor cells may interact with PD-1-expressing cells in the microenvironment to help evade immune rejection by the host.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results have been variable likely due to a lack of standardized methods for scoring and reporting stains and because there are over a dozen PD-L1 antibodies that differ in their targeted epitope, isotype, source, and binding affinity (43). Despite these limitations, moderate to high PD-L1 expression was seen in pediatric sarcomas, whereas expression in Wilms tumor was low; however expression was more likely to occur in anaplastic Wilms and was associated with an increased risk of recurrence in favorable histology tumors (38, 39, 41, 42). Importantly, pediatric tumors with the highest proportion of PD-L1 positivity showed the poorest survival (38).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in adult malignancies indicate that increased PD-L1 expression is associated with increased disease stage, presence of metastases, and refractory or relapsed disease (36, 37). Several studies have examined PD-L1 expression in pediatric solid tumors by immunohistochemistry (IHC) (Table 2) (38-42). Results have been variable likely due to a lack of standardized methods for scoring and reporting stains and because there are over a dozen PD-L1 antibodies that differ in their targeted epitope, isotype, source, and binding affinity (43).…”
Section: Introductionmentioning
confidence: 99%